Bis-benzylidine Piperidone RA190 treatment of hepatocellular carcinoma via binding RPN13 and inhibiting NF-κB signaling - Soong, Ruey-Shyang (BMC Cancer, 2020)
BACKGROUND: According to GLOBOSCAN, hepatocellular carcinoma (HCC) claimed 782,000 lives in 2018. The tyrosine kinase inhibitor sofafenib is used to treat HCC, but new anticancer agents targeting different pathways are urgently needed to improve outcomes for patients with advanced disease. The aberrant metabolism and aggressive growth of cancer cells can render them particularly susceptible to proteasome inhibition, as demonstrated by bortezomib treatment of multiple myeloma. However, resistance does emerge, and this 20S proteasome inhibitor has not proven active against HCC. The bis-benzylidine piperidone RA190 represents a novel class of proteasome inhibitor that covalently binds to cysteine 88 of RPN13, an ubiquitin receptor subunit of the proteasome’s 19S regulatory particle. RA190 treatment inhibits proteasome function, causing rapid accumulation of polyubiquitinated proteins. Considerable evidence suggests that nuclear factor κB (NF-κB) signaling, which is dependent upon the proteasome, is a major driver of inflammation-associated cancers, including HCC. METHODS: Human HCC cell lines were treated with titrations of RA190. The time course of endoplasmic reticulum stress and NF-κB-related mechanisms by which RA190 may trigger apoptosis were assessed. The therapeutic activity of RA190 was also determined in an orthotopic HCC xenograft mouse model. RESULTS: RA190 is toxic to HCC cells and synergizes with sofafenib. RA190 triggers rapid accumulation of polyubiquitinated proteins, unresolved endoplasmic reticulum stress, and cell death via apoptosis. RA190 blocks proteasomal degradation of IκBα and consequent release of NF-κB into the nuclei of HCC cells. Treatment of mice bearing an orthotopic HCC model with RA190 significantly reduced tumor growth. CONCLUSIONS: RA190 has therapeutic activity in a xenograft model, and with sorafenib exhibited synergetic killing of HCC cells in vitro, suggesting further exploration of such a combination treatment of HCC is warranted.